MODIFIKASI PERMAINAN TRADISIONAL CONGKLAK TERHADAP KEMAMPUAN BERHITUNG UNTUK MENINGKATKAN PERKEMBANGAN KOGNITIF PADA ANAK USIA DINI TAHUN 2020 - Ela Susilawati; Dian Puspitasari; Feny Kusumadewi; Lifit Nuryanih (Jurnal Ilmiah Keperawatan, 2021)
Cognitive development is a development that shows one's intellectual ability. Cognitive development in children can be improved with the traditional game and we usually called congklak . It is a simple game that trains the cognitive function of the child by knowing the numbers and also training the child's memory. This research aims to determine the influence of the traditional game on counting ability to improve cognitive development in early childhood 4-5 years in TPQ Al-Karbala and TPQ As-Syfa year 2020. The Design of this research uses the design of Quasi-Experimental Design with the approach of pre and post-test with control group design with a sample number of 38 respondents divided into 2 groups with the method probability sampling and using a measuring instrument checklist evaluation. Results showed the results of the sigma (0.000) were smaller than a (0.05) so Ha accepted Ho was rejected. In Conclusion, the results of this study show that there is an influence of cognitive development before and after given the traditional game. Suggestions, the results of this research are expected to be used as a learning media for children in improving cognitive development